Sosialisasi Pemanfaatan Media Digital untuk Pengembangan Pemasaran UMKM di Desa Cijati, Kecamatan Cimanggu, Kabupaten Cilacap - Wahid Nur Fajri; Asti Nur Afifah; Wasis Wijayanto; Riany Aulia Shabila (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Movement Indonesia's economy is supported by the micro, small, and medium enterprise sectors (SMEs). More than 97% of the national workforce is made up of SMEs, which account for about 61.07% of GDP. SMEs often face problems, such as limited market access, low capital, and low technology adoption. The use of technology in MSME marketing has a great opportunity to reach a wider market. Unfortunately, not many SMEs owners have implemented digital marketing, especially SMEs in rural areas. As in Cijati, Cimanggu, Cilacap Regency, the natural potential, processed products, and handicrafts produced by MSMEs have not been able to expand their market. produced by MSMEs have not been able to expand the market. Therefore, the socialization of utilization of digital media for the development of SMEs marketing in Cijati village was carried out to increase the understanding and ability of SMEs owners. village was conducted to increase the understanding and ability of SMEs players in the utilization of technology for digital marketing. This socialization was held on Sunday, April 9, 2023, at the Cijati, Cimanggu District, Cilacap Regency, attended by 25 SMEs owners. Participants were introduced to various digital platforms that can be used to market their products, such as social media (Facebook, Instagram, and TikTok) and e-commerce platforms (Shopee, Tokopedia, and TikTok Shop).